GUIDELINES FOR ENHANCING THE QUALITY OF WORK LIFE OF PERSONNEL IN THE KAMPHAENG PHET PROVINCIAL ADMINISTRATIVE ORGANIZATION - Suphan, Thipsuda; Vinijkul, Russadakorn (Journal of MCU Phetchaburi Review, 2025)
Abstract The objectives of this research were: 1) to study the level of quality of work life among personnel under the Kamphaeng Phet Provincial Administrative Organization, and 2) to propose guidelines for improving the quality of work life among these personnel. The population consisted of 848 personnel, with a sample size of 272 individuals. The research instrument was a questionnaire, and data were analyzed using frequency, percentage, mean, and standard deviation, as well as content analysis and thematic summarization. The research findings were as follows. 1) The quality of work life among personnel under the Kamphaeng Phet Provincial AdministrativeOrganization was found to be at a high level overall ( = 3.88, S.D. = 0.57). Interpersonal relationships within the organization ( = 4.02, S.D. = 0.68). Job security and career advancement ( = 3.44, S.D. = 0.52). Work-life balance ( = 3.80, S.D. = 0.77). Fair and adequate compensation ( = 3.50, S.D. = 0.92). And Proper and safe working environment ( = 3.36, S.D. = 0.98) 2) Key guidelines for enhancing the quality of work life among personnel of the Kamphaeng Phet Provincial Administrative Organization include: adjusting compensation to be appropriate for current economic conditions; improving the work environment to be hygienic, safe, and environmentally friendly; promoting job security and opportunities for career advancement; supporting work-life balance; and fostering positive relationships within the organization by encouraging open expression of opinions, thereby enhancing overall quality of work life in a comprehensive manner. Keywords: Improvement Guidelines / Quality of Work Life / Personnel of the Provincial Administrative Organization